INVESTIGATION OF A CRYSTALLOGRAPHIC PREFERRED ORIENTATION BY FIBRE GROWTH IN A FIBROUS QUARTZ VEIN FROM THE ORDOVICIAN OF BURKHAT PASS, KATON KARAGAI, ALTAI MOUNTAINS. - Spanov, Alikhan (Nazarbayev University School of Mining and Geosciences, 2024)
Forming such geological structures as quartz fibre veins is a well-known aspect of crystallographic preferred orientation investigation. Quartz is a crucial silica polymorph and the purest mineral in the Earth's crust due to its defective structure, making it easier to follow the deformation pattern of minerals during crystallization under different conditions (Gotze et al. 2021). Quartz crystals are located by crystallographers in the trapezohedral class of the trigonal system. It also possesses three-fold symmetry about a vertical axis, however, it has no plane of symmetry or centre of symmetry. The location of atoms and electrons in quartz was described by (Huggins, 1922). Every silicon atom is encircled by four pairs of electrons at tetrahedron corner (Figure 1). They operate like bonds that connect them to four equally distant oxygen atoms. In addition, four tetrahedrally oriented electron pairs surround every oxygen atom. Two of these pairs act as bonds that connect the oxygen with silicon atoms. Therefore, the crystal is not composed of Si02 units. However, it is a single molecule, for every bond around each silicon and oxygen atom, there is the same type of bond that connects the atoms in a molecule.
Keywords: Crystallographic preferred orientation; Altai mountain range; Thin section; Quartz veins; Type of access: Restricted